ANALISIS ARKETIPE SEPERTI TEREFLEKSI DALAM NOVEL HARRY POTTER AND THE PHILOSOPHERâ€™S STONE KARYA JK ROWLING - Mangudis, Fadhlillah Sandya; Wantasen, Isnawati L.; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â This research is entitled â€œArchetypal Analysis as Reflected in Harry Potter and the Philosopherâ€™s Stone Novel by JK Rowlingâ€. It is a research which focuses on archetypes reflected by characters in the novel by analyzing them using the concept of character analysis by Mays (2017) and archetype by Jung (1983). By finishing this research, the writer hopes that the way of how Jung described personality construction of people, could help people to understand themselves. This research uses qualitative method in analyzing the data with two steps; first, by identifying archetypes reflected by characters then the second, by analyzing the narration texts or dialogue in order to figure out the reason why it could be concluded as one of the type of archetype. The result shows that, there are twelve characters that reflected the archetypes, by analyzing the narration and dialog in the novel. Each character could have more than one type of archetype. But, not all characters in the novel could reflect the archetype as they need more narration or dialogue of experience and story in order to figure their archetype out.Keywords: Novel, Characters, Archetype